The effect of progressive weight exercises to develop endure strength and some offensive skills for Junior footballers - أ.م.د. صادق جعفر محمود (الرياضة المعاصرة)
The aim of the research is to prepare progressive weights for the development of theendure strength and some of the offensive skills of young footballers. As well as the recognition of the Effect ofthe exercises in the rise of weights in the range of force and some of the offensive skills of young footballers.